Taking a Chance: A Proposal for Contingency Fees - Tokeley, Kate (Victoria University of Wellington Law Review, 1998)
Contingency fees are a regular feature of litigation in some jurisdictions and with the increasing cost of litigating there is pressure for their acceptance in New Zealand. In this article Kate Tokeley concludes that contingency fees are an effective and ethical way to increase access to justice, particularly for indigent plaintiffs. She argues that, provided comprehensive guidelines are established, then the social advantage of using contingency fees outweighs any potential dangers. An outline of the rules and guidelines are proposed, as are enforcement mechanisms.